THE EFFECTIVENESS OF ZAKAT IN POVERTY ALLEVIATION: A META-ANALYSIS OF EMPIRICAL EVIDENCE AND AN OUTCOME-BASED FRAMEWORK FOR THE INTEGRATION OF ISLAMIC SOCIAL POLICY - Mujahidin (Academic Bright Collaboration, 2023)
Zakat is a strategic Islamic social finance instrument with strong potential to alleviate poverty, particularly in Muslim-majority countries. However, empirical evidence on zakat effectiveness remains mixed across poverty reduction, income enhancement, and mustahik empowerment outcomes. This article aims to systematically synthesize recent empirical findings on zakat effectiveness in poverty alleviation using a narrative meta-analysis approach. The manuscript is structured in accordance with the uploaded article template, covering abstract, introduction, methods, findings, discussion, conclusion, and references. This study reviews empirical works published between 2015 and 2026 from Indonesia, Malaysia, Bangladesh, and other Muslim countries. The findings indicate that zakat contributes significantly to reducing absolute poverty, increasing mustahik income, improving microenterprise access, and strengthening household social resilience. Nevertheless, its impact on poverty depth and multidimensional poverty remains highly dependent on institutional governance, productive zakat schemes, digital integration, and policy synergy. The novelty of this article lies in proposing an outcome-based zakat integration framework linking consumptive zakat, productive zakat, digital governance, and multidimensional poverty indicators. This study recommends strengthening data-driven zakat governance, improving mustahik mentoring, and integrating zakat with national social protection programs.